THE USE OF INTERACTIVE LEARNING TECHNOLOGIES IN TEACHING ANALYTICAL CHEMISTRY FOR PART-TIME PHARMACY STUDENTS - Kropelnytska, Yulia; Velyka, Alla; Stehnitska, Lyubov (SWorldJournal, 2022)
Today's pace of life prompts us to return the vector of attention in the educational medium to universal values. The primary approach to the organization of the educational process considers student-centered learning. Personality development and formatio